National Evaluation of Prescriber Drug Dispensing. Issue 10 (23rd July 2014) - Munger, Mark A.; Ruble, James H.; Nelson, Scott D.; Ranker, Lynsie; Petty, Renee C.; Silverstein, Scott; Barton, Erik; Feehan, Michael
<x xml:space="preserve">Abstract</x> Objective To describe the legal, professional, and consumer status of prescribers dispensing legend and over‐the‐counter drugs in the United States. Methods Legal and academic databases were searched to identify those states that permit prescribers to dispense medications to patients and any limitations on such practice. In addition, prescribers and patients‐consumers were surveyed to learn about the prevalence and perceptions of such practice. The use of drug samples was explicitly excluded from the study. Main Results Surveys were obtained from 556 physicians, 64 NPs, and 999 patient‐consumers of drugs dispensed by prescribers. Forty‐four states authorize prescriber dispensing. Midlevel practitioners (i.e., NPs and physician assistants) are authorized to dispense in 43 states. Thirty‐two states do not require dispensing prescribers to compete additional registration to dispense medications, and 30 states require some level of compliance with pharmacy practice requirements. Prescriber dispensing is common, independent of patient age or insurance coverage. Prescriber dispensing appears driven by physician and patient perceptions of convenience and cost reductions. Future dispensing is likely to increase due to consumers' satisfaction with the practice. Consumer self‐reported adverse drug reactions (ADRs) were equivalent between pharmacist‐ and physician‐dispensed drugs, but urgent and emergency clinic ADR consultations were slightly lower with physician dispensing. Conclusions Prescriber dispensing is firmly entrenched in the U.S. health care system, is likely to increase, does not appear to increase ADRs, and may reduce urgent care and emergency department visits. The reduction in urgent care and emergency department visits requires further study to confirm these preliminary findings.